ChemInform Abstract: Encapsulation of an Olefin Metathesis Catalyst in the Nanocages of SBA‐1: Facile Preparation, High Encapsulation Efficiency, and High Activity. Issue 51 (17th December 2013) - Yang, Hengquan; Ma, Zhancheng; Zhou, Ting; Zhang, Wenjuan; Chao, Jianbin; Qin, Yong
Abstract The catalyst can be reused for at least seven times.